2003
DOI: 10.1002/glia.10314
|View full text |Cite
|
Sign up to set email alerts
|

Activated glia induce neuron death via MAP kinase signaling pathways involving JNK and p38

Abstract: Chronic glial activation in neurodegenerative diseases contributes to neuronal dysfunction and neuron loss through production of neuroinflammatory molecules. However, the molecular mechanisms, particularly the signal transduction pathways involved in glia-dependent neuron death, are poorly understood. As a first step to address this question, we used a neuron-glia co-culture system that allows diffusion of soluble molecules between glia and neurons to test the potential importance of mitogen-activated protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 46 publications
6
111
0
Order By: Relevance
“…Increasing evidence suggests that activated microglia contribute to neuronal cell death [8][9][10][11]. For example, we [6] and Carreno-Muller et al [12] demonstrated that thrombin can cause the death of nigral dopaminergic neurons by activating microglia to produce pro-inflammatory cytokines and cytotoxic molecules.…”
mentioning
confidence: 74%
“…Increasing evidence suggests that activated microglia contribute to neuronal cell death [8][9][10][11]. For example, we [6] and Carreno-Muller et al [12] demonstrated that thrombin can cause the death of nigral dopaminergic neurons by activating microglia to produce pro-inflammatory cytokines and cytotoxic molecules.…”
mentioning
confidence: 74%
“…It is curious that LPS pretreatment of BV-2 microglia did not enhance NMDA neuronal toxicity, because LPS-activated microglia when cocultured with monotypic neurons can result in neurotoxicity (Xie et al, 2004). Aschner et al (1999) suggested that neurons in dissociated cultures are particularly susceptible to negative effects of microglia as a result of the absence of normal neuronal-glial interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection efficiency is ϳ90% (data not shown). To compare the effects of c-fms transfection with that of endotoxin, a classical stimulus for microglial activation that can induce microglial injury to monotypic neuronal cultures (Kim and Ko, 1998;Wang et al, 2002;Xie et al, 2004), some BV-2 cells were treated with 5 g/ml LPS (Sigma, St. Louis, MO). After 24 h of transfection or LPS treatment, cells were detached from the wells by mechanical pipetting, quantified, and used for assembly of the organotypic coculture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is accumulating evidence that MAP kinase activation mediates astroglial production of a host of inflammatory mediators under these conditions, which contribute to neuronal death (Migheli et al, 1997;Falsig et al, 2004). Using a special neuronglia coculture system, Xie et al (2004) demonstrated recently that lipopolysaccharide-induced activation in glia triggers neuronal death. The authors postulated that JNK activation may be part of a glial signaling pathway that leads to the release of diffusible neurotoxic molecules such as NO.…”
Section: )mentioning
confidence: 99%